Language Style Used In Elysium Movie By Neill Blomkamp - Asrawati Asrawati; Lê Thị Thanh Hai; Somayeh Bakhtiari (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study aims to identify and analyze the types of language style used by characters in Elysium, a science-fiction movie directed by Neill Blomkamp. Methodology: This research employed a qualitative descriptive method. The data were obtained from the characters’ utterances in the movie and analyzed using Martin Joos’ theory of language styles, which includes frozen, formal, consultative, casual, and intimate styles. Main Findings: The study found that all five types of language style appear in the movie. Casual style was the most frequently used, especially in conversations between close characters. Frozen and formal styles were used in official or robotic interactions, while consultative styles appeared in semi-formal settings such as workplace discussions. Intimate style was used minimally due to the nature of the film’s plot. Novelty/Originality of this study: This study contributes to sociolinguistic and stylistic analysis by applying Joos’ language style theory to modern cinematic discourse. It highlights the role of context, relationship, and setting in influencing language variation in film.